DIGITAL TALENT MANAGEMENT STRATEGIES FOR ENHANCING ORGANIZATIONAL AGILITY IN MANUFACTURING FIRMS - Gina Puspita (Journal of Management Economic and Financial, 2024)
In the era of rapid digitalization, manufacturing companies are facing pressure to improve organizational agility to remain competitive and responsive to market dynamics. This research aims to analyze how digital talent management strategies can improve organizational agility in manufacturing companies. Using a mixed-method approach, quantitative data was collected from 150 employees through a structured survey, while in-depth interviews were conducted with HR managers from leading manufacturing companies in Indonesia. Research focuses include key digital HR practices, including digital recruitment, e-learning platforms, performance analysis, and workforce planning tools. The results show that organizations that implement a comprehensive digital talent management strategy experience a significant increase in flexibility, responsiveness, and adaptability. In addition, the integration of digital HR initiatives with the organization's strategic planning strengthens the alignment between human resource capabilities and organizational goals. This study contributes to the literature with empirical evidence on the relationship between digital HR practices and organizational agility in emerging markets. In practical terms, the study offers recommendations for HR managers and executives to design and implement digital talent strategies that improve workforce performance, support innovation, and facilitate rapid decision-making. These results confirm the crucial role digital talent management plays in building resilient manufacturing organizations that are able to maintain a competitive advantage in a complex and volatile business environment